Molecular dynamics study of water and Na⁺ ions in models of the pore region of the nicotinic acetylcholine receptor - Smith, G; Sansom, M (Elsevier, 1997)
The nicotinic acetylcholine receptor (nAChR) is an integral membrane protein that forms ligand-gated and cation-selective channels. The central pore is lined by a bundle of five approximately parallel M2 helices, one from each subunit. Candidate model structures of the solvated pore region of a homopentameric (α7)5 nAChR channel in the open state, and in two possible forms of the closed state, have been studied using molecular dynamics simulations with restraining potentials. It is found that the mobility of the water is substantially lower within the pore than in bulk, and the water molecules become aligned with the M2 helix dipoles. Hydrogen-bonding patterns in the pore, especially around pore-lining charged and hydrophilic residues, and around exposed regions of the helix backbone, have been determined. Initial studies of systems containing both water and sodium ions together within the pore region have also been conducted. A sodium ion has been introduced into the solvated models at various points along the pore axis and its energy profile evaluated. It is found that the ion causes only a local perturbation of the water structure. The results of these calculations have been used to examine the effectiveness of the central ring of leucines as a component of a gate in the closed-channel model.